Effect of Long Term Storage of Soil Sample on Some Chemical Properties of Vertisol and Andosol at Kulumsa Agricultural Sub Centers - Gerenfes, Dugasa; Negasa, Gobena; Tadesse, Kassu (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted at the Kulumsa Soil and Plant Analysis Laboratory, Ethiopia from January 2021 to January 2022 to identify the appropriate storage duration of soil samples and recommend good storage materials for soil laboratories. The effects of soil sample storage on the pH, TN (%), OC (%), and available phosphorus were studied for 12 months. The highest and lowest concentrations of pH, TN (%), OC (%), and available phosphorus at the Kulumsa site were: 6.29 and 5.82; 0.17 and 0.12%; 2.93 and 1.70%; 22.53 and 10.88 respectively. At the Arsi Robe site, the highest and lowest concentrations of pH, TN (%), OC (%), and available phosphorus were 6.54 and 5.97, 0.16 and 0.12%, 3.02 and 1.00%, and 19.09 and 10.39 respectively. The highest and lowest concentrations of pH, TN (%), OC (%), and available phosphorus (mg kg1) at the Dera site were 9.14 and 8.47; 0.11, 0.07%; 4.36, 1.04%; and 111.85 and 75.37 respectively. Soil samples were stored in three storage containers with replications. The storage materials a card box with a plastic bag and a polyethylene bottle have not made any significant difference in the results of a soil sample stored under laboratory. A card box with a plastic bag was the appropriate material for soil sample storage for long-term analysis. However, based on the cost effectiveness and availability of the material to be purchased for the soil storage condition, the polyethylene plastic bag was the best option for soil sample storage under laboratory conditions.